Tratamento do lodo de resíduos de fossas e tanques sépticos em um sistema de alagado construído - Silva Junior, Édio Damásio da (2013)
The use of individual systems for treatment and disposal of sewage (ISTDS) comes as an option to the lack of sanitation in many Brazilian regions, mainly in small settlements. However, the wastes generated in these systems represent another health problem, since it contains high levels of pathogens and organic load. These wastes, termed septic tanks and cesspools residues (STCR) must be treated before their disposal to the environment. Simple and low cost technologies, like the constructed wetlands systems (CW), should be developed and evaluated aiming its implementation in small population centers. This study aimed to evaluate the treatment, more specifically the cleaning and stabilization, of the sludge accumulated in a CW designed to treat STCR. Two tanks were constructed, dug into the ground and filled with overlapping layers of gravel and sand for application and treatment of the STCR. One of them was grown by the vegetal specie Vetiver Grass (Chrysopogon zizanioides) and the other one was used as a control treatment. The STCR were applied to the system by the exhaustion of clean-pit trucks. The system behaved in vertical downward subsurface flow, controlled by a fluid spilling system. Physical-chemical and microbiological analyses of the crude residue and sludge in treatment in both tanks were made. The STCR nutritional potential was characterized through the determination of total phosphorus, total, organic and ammonia nitrogen, nitrite and nitrate. Their pathogen load was characterized by counting total coliforms, Escherichia coli, Salmonella spp. and helminths viable eggs. In addition, were characterized the attributes pH, moisture, total, volatile and fixed solids. From the sludge accumulated on the surface of treatment beds they were evaluated its pathogen load, solids content and moisture. The results were compared with the established pursuant to resolution nº 375/2006, of the brazilian National Council for the Environment (CONAMA), to verify the possibility of the sludge use in agriculture. The crude residue characterization results, showed to be similar to those cited by the literature, with high concentrations of pathogens and nutrients and also, high dispersion of values. With STCR disposals, the sludge layer increased in both systems, with higher values for the CW (about 1.1 cm per month), because of their greater capacity to retain moisture. During the disposal phase, both tanks sludge remained with high values of pathogenic organisms. At the end of the applications, there has been considerable reduction of these values, suggesting that for a better sludge treatment should be a period of "rest" without applications. It was observed that after two months of "rest", the sludge from both tanks was framed in A Class, with potential use in agriculture, as standardizes the resolution nº 375/2006 of CONAMA. In general, the tank without plants showed greater speed in the process of cleaning the sludge than the CW, mainly due to the direct sunlight exposure. However, with respect to the stabilization process, the CW was better than the control tank.